2016
DOI: 10.1007/978-3-319-33515-5_14
|View full text |Cite
|
Sign up to set email alerts
|

Key Challenges in Software Startups Across Life Cycle Stages

Abstract: Abstract. Software startups are challenging endeavours, with various road blocks on their path to success. The current understanding of the challenges that software startups may encounter is very limited. In this paper, we use the research framework of learning and product development stages to analyse the key challenges that software startups have to deal with at different life cycle stages, from problem definition to solution validation and from concept to mature product. Based on an analysis of the empirica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 7 publications
(19 reference statements)
0
47
0
Order By: Relevance
“…The configurations presented with this fsQCA analysis reinforce the approach that the implementation of management controls should be considered in accordance with the stage of the start-up company's life cycle (Wang et al, 2016). This means that each company might have control mechanisms, formal or informal, adapted to its needs.…”
Section: Drivers Of High Performancementioning
confidence: 58%
See 1 more Smart Citation
“…The configurations presented with this fsQCA analysis reinforce the approach that the implementation of management controls should be considered in accordance with the stage of the start-up company's life cycle (Wang et al, 2016). This means that each company might have control mechanisms, formal or informal, adapted to its needs.…”
Section: Drivers Of High Performancementioning
confidence: 58%
“…However, they should be used once there is a routine (Abernethy & Brownell, 1997). Thus, the stage of the life cycle in which the firm finds itself should be borne in mind when this approach is addressed (Wang, Edison, Bajwa, Giardino, & Abrahamsson, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Da Silva et al [34] adduced pricing issues, market validation and ignorance of customers' demands as main problems causing startup failures. Wang et al [35] confirmed the fitting of the products on the market as an important problem of the startups adding also the functionality of the business model and issues with the acquisition of customers. Giardino et al [36] also included targeting toospecialized markets to the list of significant issues of startups causing their failure.…”
Section: Courses Supporting Entrepreneurial Educationmentioning
confidence: 99%
“…Characteristics typically associated with startups include (1) highly reactive, (2) innovation, (3) uncertainty, (4) rapidly evolving, (5) time-pressure, (6) third party dependency, (7) small team, (9) one product), (10) low-experienced team, (11) new company, (12) flat organization, (13) highly risky, (14) not self-sustained, (15) lack of resources, and (16) little working history [8]. In software startups, the role of software in the final offering may vary from being the core product to merely serving as an enabler or support of the main business idea (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In software startups, the role of software in the final offering may vary from being the core product to merely serving as an enabler or support of the main business idea (e.g. Uber) [11]. Klotins [3] highlighted the (lack of) empirical evidence behind many of these characteristics, questioning the uniqueness of software startups in relation to failure rates, lack of software engineering (SE) experience, innovativeness, market-related time pressure, and lack of resources.…”
Section: Introductionmentioning
confidence: 99%